Anti-corrosion wear-resistant coatings on parts of oil field equipment - Eremin, E. N.; Yurov, V. M.; Ibatov, M. K.; Guchenko, S. A.; Laurynas, V. Ch. (SPIE-INT SOC OPTICAL ENGINEERING, 2016)
The paper reports on the preparation of ion-plasma anti-corrosion and wear-resistant coatings Cr-Mn-Si-Cu-Fe-Al and Cr-Mn-SiCu-Fe-Al-Ti. The first coating is prepared using the composite cathode. The second coating is prepared by simultaneous sputtering of composite and titanium cathodes in nitrogen atmosphere. In both cases the cellular microstructure of coatings is observed. The nanohardness of coating Cr-Mn-Si-Cu-Fe-Al, which is 7.4 GPa, is nearly two times as high as the nanohardness of titanium being 4.1 GPa and almost the same as for multilayer film Ti/D-& ɇZKLFKLV *3D 7KHFRUURVLRQUDte in sulfuric acid (53 wt.%) is about 0.02 mm/year. The nanohardness of coating Cr-Mn-Si-Cu-Fe-Al+Ti, being 14.2 GPa, is nearly equal to the nanohardness of amorphous ribbon Zr-Cu-Ti-Ni, being 14.5 GPa or silicon (100), which is 14.8 GPa. The corrosion rate in sulfuric acid (53 wt.%) is less than 0.01 mm/year. The multilayer film of Ti/D-& ɇDQGDPRUSKRXVWDSH=U-Cu-Ti-Ni are used as abrasives, but their preparation is ten times more expensive than the proposed coatings.
Keywords: anti-corrosion coating; wear-resistant coating; composite cathode; nanohardness; cellular structure